2005
DOI: 10.1056/nejmoa043690
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemic Hypoglycemia with Nesidioblastosis after Gastric-Bypass Surgery

Abstract: We describe six patients (five women and one man; median age, 47 years; range, 39 to 54) with postprandial symptoms of neuroglycopenia owing to endogenous hyperinsulinemic hypoglycemia after Roux-en-Y gastric bypass surgery. Except for equivocal evidence in one patient, there was no radiologic evidence of insulinoma. Selective arterial calcium-stimulation tests, positive in each patient, were used to guide partial pancreatectomy. Nesidioblastosis was identified in resected specimens from each patient, and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
485
4
37

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 709 publications
(539 citation statements)
references
References 21 publications
13
485
4
37
Order By: Relevance
“…Service and colleagues reported that six patients after Roux-en-Y gastric bypass surgery had postprandial hypoglycemia and neuroglycopenia with elevated insulin levels that led surgeons to perform partial pancreatectomies for control of symptoms (Service et al, 2005). Therefore pancreatic specimens were available for histological evaluation and the patients were diagnosed as having nesidioblastosis and enlarged islets.…”
Section: Potential Glp-1r Effects After Gastric Bypass Surgerymentioning
confidence: 99%
“…Service and colleagues reported that six patients after Roux-en-Y gastric bypass surgery had postprandial hypoglycemia and neuroglycopenia with elevated insulin levels that led surgeons to perform partial pancreatectomies for control of symptoms (Service et al, 2005). Therefore pancreatic specimens were available for histological evaluation and the patients were diagnosed as having nesidioblastosis and enlarged islets.…”
Section: Potential Glp-1r Effects After Gastric Bypass Surgerymentioning
confidence: 99%
“…11,30,31 In 2005, Service et al 30 reported in the New England Journal of Medicine 11 the details of six such cases, which these authors deemed adultonset nesidioblastosis, and which were severe enough to require partial pancreatectomy. Several other groups have since reported similar observations.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
“…30,31 Identifying these putative molecules could lead to new medical strategies to reverse the progressive b-cell failure that defines T2DM. Other investigators, however, claimed that pancreas samples from afflicted patients showed no increases in b-cell mass or proliferation beyond those expected from obesity, and therefore that the syndrome must arise from inappropriately increased b-cell function.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism postulated to improve diabetes after gastric bypass is an augmented incretin response; postprandial plasma concentrations of the potent incretin glucagon-like peptide-1 rise after gastric bypass [2]. Recently hyperinsulinaemia and hypoglycaemia have been recognised as new complications of gastric bypass [3,4]. Patients have presented with hypoglycaemia associated with confusion, syncope and seizures attributed to changes in glucose homeostasis [5].…”
Section: Introductionmentioning
confidence: 99%